The essential Dick Gregory - Gregory, Dick 1932-2017 (Amistad, an imprint of HarperCollinsPublishers, 2022)
"A true renaissance man, Richard Claxton "Dick" Gregory was one of the pioneering satirists of his generation, a reformer and brilliant spokesperson for the downtrodden and forgotten who dedicated his life to speaking unadulterated truth--and to improving ordinary lives. A revered human rights and environmental activist, fearsome and uncompromising social critic, lauded bestselling author, and beloved nutrition guru, Gregory aimed not only to educate souls, but to liberate them. His words shaped a generation and remain vital for our own turbulent times, offering wisdom to enlighten and inspire a new activist age. This carefully curated anthology of selected writings reflects and celebrates Dick Gregory's wisdom and his vision. Divided into three sections--Body, Mind, and Spirit--it includes previously unavailable transcriptions and excerpts taken from his sixteen books, fifteen albums and audio compilations, and more than 1,200 hours of archival video, including lectures, interviews, and comedic performances. It is a breathtaking tour through the life of one of America's most prophetic and relevant cultural icons. This volume is a pointillistic portrait of a man who gave up a lucrative entertainment career to fight injustice on the front line of battle--leading protests and hunger strikes to end the Vietnam War and apartheid in South Africa; supporting civil rights, feminism, and Native Americans; and addressing hunger, poverty, and police brutality."
Keywords: Gregory, Dick -- 1932-2017; Geschichte 1962-1983; Politik; Gesellschaft; USA; Gregory, Dick / Literary collections; Gregory, Dick; Essays; Literary collections; Anthologie; Quelle